Peran Guru Dalam Meningkatkan Prestasi Belajar Peserta Didik di RA. Dharma Wanita Kemenag Kabupaten Jeneponto - lina, Nur; Muhaemin, Muhaemin Badaruddin; Untung, Untung; Alamsyah, Muhammad Nur (UNIVERSITAS NEGERI MAKASSAR, 2025)
This research examines the role of teachers in improving student learning achievement at Dharma Wanita Kemenag Jeneponto Regency. The research subjects were 3 people consisting of 1 principal and 2 educators/teachers. Data collected through observation, interviews and documentation. Data is processed through data reduction procedures, data presentation, and drawing conclusions and verification. The research results show that there are several roles for teachers in improving students' learning achievements, including 1) As a motivator, teachers give praise and make students active in the learning process so as to increase enthusiasm in students. 2) As a manager, by giving assignments and tests, it becomes an assessment for teachers/educators to monitor student development.